Pt States in BaCe0.98Pt0.02O3-delta during start up and shut down operations under different conditions: stability and activity of ionic Pt in water gas shift reaction - Rajesh, Thattarathody; Devi, R. Nandini (Catalysis Letters, 2014)
Stability of Pt species in doped BaCeO3 perovskites under Water gas shift reaction conditions is studied using X-ray absorption spectroscopy and in situ powder X-ray diffraction. The catalyst BaCe0.98Pt0.02O3-delta has Pt in +2 oxidation state and is found to be stable in the ionic form under reaction conditions as well as under various highly reducing shut down and start up conditions. In-situ XRD under Water Gas shift reaction conditions also reveals the Pt ions to be highly stabilized in lattice and no egress is observed.
Keywords: BaCeO3; Deactivation; platinum; WGS reaction; XPS